2013
DOI: 10.1007/s12032-013-0466-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and survival in patients with melanoma brain metastases

Abstract: Brain metastases (BM) are one of the most frequent neurological complications of cancers. Melanoma is the third most common tumor to metastasize to the brain with a reported incidence of 10-40 %, and many patients have subclinical BM (>73 %). We computer-searched the clinical records of all our patients registered into a database to identify patients that presented or developed BM. A total of 49 patients with melanoma BM were included in our analysis. General time to brain metastases (TTBM) was 23 months. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
6
25
2
Order By: Relevance
“…In the literature, extracranial metastatic involvement is reported in 65-83% (10,37,39,43,45) of patients and in 37-51% of cases, multiple organ systems are affected by extracerebral metastasis (10,37). In 22% of the patients in our study, lymph nodes were positive for metastasis upon initial diagnosis of melanoma and 61% of patients developed metastatic spread to lymphatic nodes during their disease course which stands in line with current literature, reporting lymph node metastasis in 24-54% (17,39).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the literature, extracranial metastatic involvement is reported in 65-83% (10,37,39,43,45) of patients and in 37-51% of cases, multiple organ systems are affected by extracerebral metastasis (10,37). In 22% of the patients in our study, lymph nodes were positive for metastasis upon initial diagnosis of melanoma and 61% of patients developed metastatic spread to lymphatic nodes during their disease course which stands in line with current literature, reporting lymph node metastasis in 24-54% (17,39).…”
Section: Discussionsupporting
confidence: 91%
“…Fife et al reported a median age at the time of diagnosis of brain metastasis of 49 and 57 years with a median time from initial diagnosis of melanoma until occurrence of cerebral metastasis of 2.5 and 3.7 years (10). In our study, patients were older when brain metastasis was confirmed (62 years), however, median time to development of cerebral metastasis (2.5 years in our patient group) was comparable with current literature (1.9-2.7 years) (17,18,37,39).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations